GENERATION MEAN ANALYSIS FOR GRAIN YIELD IN MAIZE - M. I. U. Haq; S. Ajmal; N. Kamal; S. Khanum; M. Siddique; M. Z. Kiani (Journal of Animal and Plant Sciences, 2013)
The present study was conducted to evaluate genetic and epistatic effects governing the inheritance of grain yield and yield components. Parental material comprising of six genetically different maize inbred lines were crossed to produce F1, F2 and backcross generations. The analysis of variance showed significant differences among generations. Generation mean analysis revealed the preponderance of non-additive effects for all the characters under study. Please revisit. l (dom×dom) component was significant in all three traits with exceptions of few crosses. While i (ad × ad) was significant only for grain yield and in only one cross for 100-grain weight. The opposite of sign of h and l indicated the presence of duplicate epistasis. Significant role of dominance variance along with duplicate epistasis in the inheritance of said characters favours the use of research material (maize inbred lines) for the development of single cross hybrids.
Keywords: Inbred lines; Generation mean analysis; Dominance; Additive; Epistasis